Longshore and Rip Currents during High Tide at Bangsaen Beach, Chonburi Province - Buranapratheprat, Anukul; Suntra-rachun , Palita (Burapha Science Journal, 2026)
The researchers measured longshore and rip currents during high tide at Bangsaen Beach using weighted plastic bottles that were released in nearshore zone during high tide. The currents were measured once a month from April 2014 to March 2015 to cover the different seasons of the year. Longshore current flowed along the beach toward Lam Tan or the north of Bangsaen Beach during the southwest monsoon season and flowed back to Won Napa Beach or the south of Bangsaen Beach during the northeast monsoon season. Uncertain direction of the longshore flows occurred during the inter-monsoon periods. Rip current also occurred at the beach but was not very strong. This current well formed during the late southwest monsoon and the inter-monsoon period from the southwest to the northeast monsoon seasons in the area from Bangsaen Road Circle to Laem Tan. The results made us understand the trend of sand transport along Bangsaen Beach each season. Sand tends to move along the beach towards Lam Tan during the southwest monsoon and move back to Won Napa Beach during the northeast monsoon. This information is significant for understanding the shoreline dynamics of Bangsaen Beach which is useful for the mitigation of coastal erosion in the area.